Influence of template properties and quantum well number on stimulated emission from Al0.7Ga0.3N/Al0.8Ga0.2N quantum wells. (20th February 2018) - Jeschke, J; Martens, M; Hagedorn, S; Knauer, A; Mogilatenko, A; Wenzel, H; Zeimer, U; Enslin, J; Wernicke, T; Kneissl, M; Weyers, M
Abstract: AlGaN multiple quantum well laser heterostructures for emission around 240 nm have been grown by metalorganic vapor phase epitaxy on epitaxially laterally overgrown (ELO) AlN/sapphire templates. The edge emitting laser structures showed optically pumped lasing with threshold power densities in the range of 2 MW cm −2 . The offcut angle of the sapphire substrates as well as the number and the width of the quantum wells were varied while keeping the total thickness of the gain region constant. A larger offcut angle of 0.2° leads to step bunching on the surface as well as Ga accumulation at the steps, but also to an increased inclination of threading dislocations and coalescence boundaries resulting in a reduced dislocation density and thus a reduced laser threshold in comparison to lasers grown on ELO with an offcut of 0.1°. For low losses, samples with fewer QWs exhibited a lower lasing threshold due to a reduced transparency pump power density while for high losses, caused by a higher threading dislocation density, the quadruple quantum well was favorable due to its higher maximum gain.